Are AudioviSual maTERials disseminated via sOcIal meDia effective to improve evidence-based rehabilitation implementation for physiotherapists (ASTEROID trial)? A feasibility study - Myllena M. G. Fernandes; Anna Carolina O. Machado; Maurício S. Fanfa; Ada C. M. Silveira; Rafaela A. Schreiner; Anna Julia Meireles Dangui; Maitê M. Pellenz; Daniela Rigo; Luiza Marx Matte; Emilly Renk Mello; Ane Priscila Diel; Brenda D. Guterres; et al. (BMC Research Notes)
Abstract Objective The present study aimed to evaluate the feasibility of an educational program disseminated via social media to improve the scientific and technical knowledge of physiotherapists. Results In this single-group interventional feasibility study, practicing physiotherapists participated in a 10-week Instagram-based program, which included 20 infographics posted twice weekly. Feasibility was evaluated using the RE-AIM framework (Reach, Effectiveness, Adoption, Implementation, and Maintenance). After the intervention, semi-structured interviews were conducted to gather feedback on participant experiences. Of the 30 physiotherapists recruited, 15 initiated the program, and 8 (53%) completed it. No significant differences were observed between pre- and post-program scores on effectiveness outcomes related to perceptions, utilization, and understanding of scientific information for clinical practice. While 63% of participants reported that the program helped them overcome barriers to EBP, overall perceptions and behaviors showed minimal change. Nonetheless, all participants recognized a positive impact on their clinical practice, with 50% reporting that they applied program content to their work. Although 63% indicated they would maintain their approach to studying technical content, all participants affirmed their intention to use resources that facilitate knowledge acquisition. Feedback from interviews indicated positive attitudes towards social media-based educational programs.